An empirical investigation of banking customers’ perception of the viability of Islamic banking in Côte d’Ivoire - Adewale, Abideen Adeyemi; Zare, Ibrahim (IIUM Press, 2015)
This study empirically examines the perceptions of bank customers in Côte d’Ivoire on the viability of Islamic banking in the country. Specifically, the study investigates the level of awareness of the bank customer respondents about Islamic banking as well as the factors that motivate their patronage. A sample of 274 respondents residing in Abidjan, Côte d’Ivoire took part in this research. The data elicited via an adapted research instrument is subjected to both descriptive and inferential statistics using IBM SPSS AMoS software version 21. The results reveal that most of the Ivorian bank customers are aware of Islamic banking but lack knowledge about its operation. Moreover, the customers indicate commendable willingness to patronize the Islamic banks when established in Côte d’Ivoire as long as it is not relatively costlier to do so. The likely patronage-influencing factors include religion, banking-related and customer-related factors, and societal norms. Recommendations based on research findings are also offered.